Data Mining Tempat Penampungan Sampah Sementara (TPS) Di Wilayah Jakarta Tahun 2019 Dengan Menggunakan Metode Regresi Linear Sederhana - abiyan, rifqi zaidan (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2025)
The waste collection stage at temporary waste storage sites (TPS) is an aspect of waste management that requires very special attention in order to improve waste characteristics. This study aims to determine how community behavior in disposing of waste at Temporary Disposal Sites (TPS) will naturally impact the environmental conditions of those sites. Ineffective management of these storage sites has led to environmental and public health problems in Jakarta. Sustainable solutions—such as the application of advanced technology and active community involvement—are therefore crucial to building a responsive waste management system. This study provides insights into the dynamics of waste storage sites in Jakarta, with the goal of contributing to more effective and integrated policy planning to meet the challenges of waste management in this rapidly growing city.